2022
DOI: 10.2807/1560-7917.es.2022.27.30.2200559
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination and BA.1 breakthrough infection induce neutralising antibodies which are less efficient against BA.4 and BA.5 Omicron variants, Israel, March to June 2022

Abstract: This work evaluated neutralising antibody titres against wild type (WT) SARS-CoV-2 and four Omicron variants (BA.1, BA.2, BA.4 and BA.5) in healthcare workers who had breakthrough BA.1 infection. Omicron breakthrough infection in individuals vaccinated three or four times before infection resulted in increased neutralising antibodies against the WT virus. The fourth vaccine dose did not further improve the neutralising efficiency over the third dose against all Omicron variants, especially BA.4 and BA.5. An Om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 10 publications
0
27
1
Order By: Relevance
“…Recent discoveries of the sublineages BA.4 and BA.5 have raised several concerns, including greater transmissibility, greater resistance to vaccines, and an increased risk of reinfection ( 33 ). In recent studies, researchers have discovered that these two sublineages, BA.4 and BA.5, are linked to an increased risk of reinfection following vaccination and exhibit distinct pathogenic characteristics ( 34 , 35 , 36 ). Due to their ability to resist antibodies produced by vaccination and previous infection, they may cause a new wave of infection ( 34 , 35 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent discoveries of the sublineages BA.4 and BA.5 have raised several concerns, including greater transmissibility, greater resistance to vaccines, and an increased risk of reinfection ( 33 ). In recent studies, researchers have discovered that these two sublineages, BA.4 and BA.5, are linked to an increased risk of reinfection following vaccination and exhibit distinct pathogenic characteristics ( 34 , 35 , 36 ). Due to their ability to resist antibodies produced by vaccination and previous infection, they may cause a new wave of infection ( 34 , 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, researchers have discovered that these two sublineages, BA.4 and BA.5, are linked to an increased risk of reinfection following vaccination and exhibit distinct pathogenic characteristics ( 34 , 35 , 36 ). Due to their ability to resist antibodies produced by vaccination and previous infection, they may cause a new wave of infection ( 34 , 35 ). In addition to increased transmission, morbidity, and mortality, these VOCs impair diagnosis, cause reinfection in previously infected individuals, and lead to vaccine breakthroughs in fully vaccinated individuals ( 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Future vaccines will have to be built on the aminoacidic sequence of newer Omicron sub-variants in order to elicit a more robust antibody response [10] and to avoid immune evasion [11] , [12] , [13] . Indeed, a national surveillance consortium for SARS-CoV-2 sequencing established in Israel evaluated neutralizing antibody titres against wild type SARS-CoV-2 and four Omicron variants (BA.1, BA.2, BA.4 and BA.5) in healthcare workers who had breakthrough BA.1 infection [14] .…”
mentioning
confidence: 99%
“…Briefly, Kliker and co-workers demonstrated that Omicron breakthrough infection in individuals vaccinated three or four times before infection resulted in increased neutralising antibodies against the wild type virus [14] . Notably, the fourth dose of vaccine did not further improve the neutralising efficiency over the third dose against all Omicron variants [14] .…”
mentioning
confidence: 99%
“…There is still very limited information about the neutralisation efficiency of vaccinated individuals against BA.2.75. To address this, we used here the same methods that were used previously, to elucidate the vaccine effectiveness against BA.5 [ 2 ].…”
mentioning
confidence: 99%